The possible interaction between periostin expressed by cancer stroma and tumor‐associated macrophages in developing mycosis fungoides. Issue 2 (23rd November 2015) - Furudate, Sadanori; Fujimura, Taku; Kakizaki, Aya; Kambayashi, Yumi; Asano, Masayuki; Watabe, Akiko; Aiba, Setsuya
Abstract: Mycosis fungoides (MF) starts as an indolent disease, progresses from a patch stage to confluent plaques and ultimately develops skin tumors. Tumor‐associated macrophages (TAMs) play roles in maintaining the tumor microenvironment in MF. The purpose of this study was to elucidate the involvement of TAMs in the lesional skin of different stages of MF. First, we immunohistologically examined the percentage of CD163 + macrophages and CD206 + cells, as well as the levels of periostin and IL‐4 in cancer stroma. The percentage of CD206 + cells increased in parallel with tumor progression, while there was no significant difference in the percentage of CD163 + cells. Periostin was prominent in the stromal area at the patch and plaque stages but decreased at the tumor stage. In contrast, IL‐4 was prominently stained at both plaque and tumor stages. To further elucidate the molecular mechanisms of the effects of these stromal factors on TAMs, we examined their effects on mRNA expression in monocyte‐derived macrophages in vitro . Based on microarray analysis and gene ontology, we examined a series of chemokines and MMPs whose expression was strongly connected with periostin stimulation. The DNA microarray results were verified in M2 macrophages using real‐time PCR. We further examined the mRNA expression of these chemokines and MMPs in the presence of periostin and IL‐4 to simulate the advanced stages of MF and validated their protein expression by ELISA. Our present report suggests possible roles of periostin on TAMs in establishing the tumor microenvironment in MF.